2006
DOI: 10.1161/01.atv.0000246779.78003.cf
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Antigen R, an RNA-binding Protein, in Mediating the Stabilization of Toll-Like Receptor 4 mRNA Induced by Endotoxin

Abstract: Objective-Lipopolysaccharide (LPS) interacts with toll-like receptor 4 (TLR4) and induces proliferation of vascular smooth muscle cells (VSMCs) which plays a causal role in atherogenesis. See page 2582Previous studies have demonstrated that TLR4 is expressed abundantly in failing myocardium 6 and in macrophages infiltrated into human and murine lipid-rich atherosclerotic lesions. 7 The functional expression of TLR4 and subsequent augmentation of intimal hyperplasia have recently been described. 8 Hypoxia dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 38 publications
0
59
1
Order By: Relevance
“…Rac can also regulate mRNA stability, [26][27][28] and the cyclin D1 3'-UTR contains AU-rich elements which can recruit RNA stabilizing proteins. 29 We therefore determined the effect of Rac on the half-life of cyclin D1 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Rac can also regulate mRNA stability, [26][27][28] and the cyclin D1 3'-UTR contains AU-rich elements which can recruit RNA stabilizing proteins. 29 We therefore determined the effect of Rac on the half-life of cyclin D1 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…The HuR is an RNA binding protein that enhances the stability of target mRNAs (26,27). It has been shown that activation of the p38 MAPK pathway results in the translocation of HuR from the nucleus to the cytoplasm where it binds to the 3 ¶-untranslated regions (UTR) of various mRNAs containing a core AUUUA sequence (20,(28)(29)(30)(31). The p75 NTR transcript contains two AUUUA sites in the 3 ¶-UTR, suggesting HuR binding as a possible mechanism by which Rflurbiprofen and ibuprofen may stabilize p75 NTR mRNA.…”
Section: R-flurbiprofen and Ibuprofen Increase P75mentioning
confidence: 99%
“…Moreover, siRNA knockdown of both MK2 and MK3 together prevents induction of p75 NTR by R-flurbiprofen or ibuprofen to a greater extent than knockdown of either MK2 or MK3 separately, indicating that p38 MAPK is able to induce p75 NTR by acting through both MK2 and MK3 (Quann et al, 2007b). The mRNA stabilizing effects of the p38 MAPK pathway (Ronkina et al, 2007) also involves the RNA binding protein HuR (Tran et al, 2003;Lin et al, 2006;Jin et al, 2007;Song et al, 2005). Its ability to stabilize target mRNAs is linked to its subcellular localization, and activation of p38 MAPK and MK2 have been shown to cause translocation of HuR from the nucleus to the cytoplasm, resulting in increased mRNA stability of a number of p38 MAPK regulated genes (Tran et al, 2003;Lin et al, 2006;Jin et al, 2007;Song et al, 2005).…”
Section: Nsaid Induced Phosphorylation Of P38 Mapk Is Necessary For Imentioning
confidence: 99%
“…The mRNA stabilizing effects of the p38 MAPK pathway (Ronkina et al, 2007) also involves the RNA binding protein HuR (Tran et al, 2003;Lin et al, 2006;Jin et al, 2007;Song et al, 2005). Its ability to stabilize target mRNAs is linked to its subcellular localization, and activation of p38 MAPK and MK2 have been shown to cause translocation of HuR from the nucleus to the cytoplasm, resulting in increased mRNA stability of a number of p38 MAPK regulated genes (Tran et al, 2003;Lin et al, 2006;Jin et al, 2007;Song et al, 2005). HuR has repeatedly been shown to stabilize transcripts containing the AUUUA sequence (Tran et al, 2003;Song et al, 2005).…”
Section: Nsaid Induced Phosphorylation Of P38 Mapk Is Necessary For Imentioning
confidence: 99%